Skills and competences of audio describers in Spain - Mendoza, Nuria; Matamala, Anna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article describes the skills and competences that professional audio describers should acquire, based on the results of a questionnaire and on interviews with lecturers of AD courses in the context of Spanish MAs. First, the input provided by audio describers and end-users for a questionnaire conducted under ADLAB PRO, an Erasmus+ project funded by the European Commission, is discussed; it focuses on data from Spanish participants. Secondly, the skills and competences identified through the questionnaire are compared to those included in specific courses on audio description within MA programmes offered at Spanish universities. The article begins with a brief discussion of terminology and ends with a discussion on how the results of our research could have an impact on training proposals for AD.